Controlling feeding practices and maternal migrant background: an analysis of a multicultural sample. Issue 5 (21st November 2016) - Somaraki, Maria; Eli, Karin; Ek, Anna; Lindberg, Louise; Nyman, Jonna; Marcus, Claude; Flodmark, Carl-Erik; Pietrobelli, Angelo; Faith, Myles S; Sorjonen, Kimmo; Nowicka, Paulina
Abstract: Objective: Parental feeding practices shape children's relationships with food and eating. Feeding is embedded socioculturally in values and attitudes related to food and parenting. However, few studies have examined associations between parental feeding practices and migrant background. Design: Cross-sectional study. Parental feeding practices (restriction, pressure to eat, monitoring) were assessed using the Child Feeding Questionnaire. Differences were explored in four sub-samples grouped by maternal place of birth: Sweden, Nordic/Western Europe, Eastern/Southern Europe and countries outside Europe. Crude, partly and fully adjusted linear regression models were created. Potential confounding variables included child's age, gender and weight status, and mother's age, weight status, education and concern about child weight. Setting: Malmö and Stockholm, Sweden. Subjects: Mothers ( n 1325, representing seventy-three countries; mean age 36·5 years; 28·1 % of non-Swedish background; 30·7 % with overweight/obesity; 62·8 % with university education) of pre-school children (mean age 4·8 years; 50·8 % boys; 18·6 % with overweight/obesity). Results: Non-Swedish-born mothers, whether European-born or non-European-born, were more likely to use restriction. Swedish-born mothers and Nordic/Western European-born mothers reported lower levels of pressure to eat compared with mothers born in Eastern/Southern Europe and mothers born outside Europe. Differences in monitoring were small. Among the potential confounding variables, child weight status and concern about child weight were highly influential. Concern about child weight accounted for some of the effect of maternal origin on restriction. Conclusions: Non-European-born mothers were more concerned about children being overweight and more likely to report controlling feeding practices. Future research should examine acculturative and structural factors underlying differences in feeding.